Plant Endophytic Fungus Extract ZNC Improved Potato Immunity, Yield, and Quality - Cao, Juan; Liu, Baoyou; Xu, Xinning; Zhang, Xiaoying; Zhu, Changxiang; Li, Yang; Ding, Xinhua (Frontiers in Plant Science, 2021)
Endophytic fungi play an important role in plant survival and reproduction, but the role of their metabolites in plant growth and immunity, as well as in crop quality formation, is poorly understood. Zhinengcong (ZNC) is a crude ethanol extract from the endophytic fungus Paecilomyces variotii, and previous studies have shown that it can improve the growth and immunity in Arabidopsis thaliana. The aim of the study was to reveal the trade-off balance between plant growth and immunity by evaluating the mechanisms of ZNC on potato growth, yield, and priming immunity against the oomycete Phytophthora infestans indoors and in the field. ZNC maintained a good balance between plant growth and resistance against P. infestans with high activity. It induced the reactive oxygen species (ROS) production, promoted plant growth, yield and quality parameters, enhanced the expression of indoleacetic acid (IAA) related genes, and increased the absorption of nitrogen from the soil. Moreover, the plant endophytic fungus extract ZNC stimulated the pathogen-associated molecular pattern (PAMP) triggered immunity (PTI) pathway and contributed to the ZNC-mediated defense response. Two years of field trials have shown that irrigation with ZNC at one of two optimal concentrations of 1 or 10ng/ml could significantly increase the output by 18.83% or more. The quality of potato tubers was also greatly improved, in which the contents of vitamin C, protein, and starch were significantly increased, especially the sugar content was increased by 125%. Spray application of ZNC onto potato plants significantly reduced the occurrence of potato blight disease with 66.49% of control efficacy at 200ng/ml and increased the potato yield by 66.68% or more in the field. In summary, plant endophytic fungus extract ZNC promoted potato immunity, yield, and quality and presented excellent potential in agricultural applications.